Tanzania Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As part of the US government’s Feed the Future initiative that aims to address global hunger and food security issues in sub-Saharan Africa, the US Agency for International Development is supporting three multi-stakeholder agricultural research projects under Africa Research In Sustainable Intensification for the Next Generation (Africa RISING - AR) program. The overall aim of the program is to transform agricultural systems through sustainable intensification projects in Ghana, Ethiopia, Tanzania, Malawi, Mali, and (potentially) Zambia. In Tanzania, the project, led by the International Institute of Tropical Agriculture (IITA), will be supporting cereal-based farming systems. Multiple participatory and adaptive agricultural interventions are currently taking place in Babati, Kongwa, and Kiteto, three districts in Tanzania, led by researchers from the IITA. Experts from IITA have supported or introduced intercropping, drought-tolerant crop varieties, water harvesting practices, and organic fertilizer application. The International Food Policy Research Institute (IFPRI) leads the monitoring and evaluation (M&E) activities of the AR program. As part of the M&E activities in Tanzania, IFPRI contracted Economic Development Initiatives (EDI) to conduct baseline household and community surveys in Babati, Kongwa, and Kiteto districts. The main objective of this survey is to collect high-quality baseline household data to support the M&E activities of the AR program in Tanzania. More specifically, the survey aims to collect detailed information on the composition of the household, employment, health, agriculture, income and expenditures, credit, assets, subjective welfare and food security, shocks, and the anthropometric status of children and women.